Fuzzy-pid controller design for brake-by-wire system of electrical vehicle - Sider, Ameer M. F. (2014)
This study presents Fuzzy-PID controller design for brake-by-wire of electric vehicle.BBW is a new brake technology in which mechanical and hydraulic components of traditional brake systems are replaced by electric circuits and devices to carry out the function of braking in a vehicle by wire-transmitted information. The advantages of electronic devices such as reducing vehicle weight and increasing brake performance are considered the main purposes trend of automotive industry towards this new brake technology. The motivation of this study is to enhance the safety aspects for the vehicle while attaining any desired speed. To achieve that, an optimal brake force at different road types and conditions and for different brake commands must be obtained within a reasonable time and without vehicle sliding.he aforementioned matters are accomplished essentially by obtaining mathematical modeling of the vehicle-wheel dynamics based on braking characteristics behavior. The derived model after that is utilized to construct two different BBW systems named as hard brake and normal brake system to handle and meet various brake situations and conditions which they are built according to the selected state dynamics of each system. In view of that, the mechanism behavior and operating process of both brake systems are dominated by implementing distinct control algorithms based on PID and Fuzzy-PID controllers. Indeed, the fundamental objective of the applied control methods is to attainesired vehicle speed from one side and to maintain vehicle stability and controllability from other side. Above and beyond, BBW operating process is improved by developing new integrated control strategy that involves both designed brakes (hard and normal) in one sole framework. Constructing such a system is primarily based on conventional IFELSE conditional control. Nonetheless, the braking operation of the proposed BBW systems is carried out by utilizing permanent magnetic DC motor according to the predetermined control signal. The simulation analysis of the proposed BBW schemes and their controllers are conducted on MATLAB software using Simulink tool, where five road types and conditions (asphalt (dry, wet), cobblestone (dry, wet) and concrete) are engaged in theanalysis and investigation of the output behavior of the plant and its operating process. Moreover, the study presents supplementary explanation about performance of the proposed actuator (PMDC) as well as about the process of braking mechanism. The simulation results and outcomes demonstrate efficient operating brake systems that lead to obtain desired vehicle speed successfully within reasonable brake time. This is a clear evidence of obtaining safety aspects of the vehicle as well as passengers since control strategy could maintain optimal brake force that leads to shorter stopping distance, hence increasing safety aspects. Furthermore, the ability of proposed control strategies to operate during various situations (hard or normal brake request) at different road conditions is also achieved effectively. Consequently, the aim of the study which is designing electronically brake system for BBW of electric vehicle that can operate in different brake situations and at different road conditions is successfully accomplished and achieved. Finally, after the analysis and discussion of BBW and controller design, suggestions for key future development and enhancement of the current study are presented such as implementing adopted BBW design practically.